The Impact of Lockdown on eBC Mass Concentration over a Semi-arid Region in Southern India: Ground Observation and Model Simulations - Surya Nagi Reddy Palle; Chakradhar Rao Tandule; Raja Obul Reddy Kalluri; Balakrishnaiah Gugamsetty; Rama Gopal Kotalo; Lokeswara Reddy Thotli; Bhavyasree Akkiraju; Siva Sankara Reddy Lingala (Aerosol and Air Quality Research)
Abstract In the present study, we focused on the impact of lockdown on black carbon (eBC) mass concentrations and their associated radiative implications from 01st March to 30th June 2020, over a semi-arid station, i.e., in the district of Anantapur in Southern India. The mean eBC mass concentration was observed before lockdown (01st–24th March 2020) and during the lockdown (25th March–30th June 2020) period and was about 1.74 ± 0.36 and 1.11 ± 0.14 μg m−3, respectively. The sharp decrease (~35%) of eBC mass concentration observed during the lockdown (LD) period as compared with before lockdown (BLD) period, was mainly due to the reduction of anthropogenic activities and meteorology. Furthermore, during the entire LD period, the net composite forcing at the top of the atmosphere (TOA) and at the surface (SUR) varied from −4.52 to −6.19 Wm −2 and −22.91 to −29.35 Wm −2, respectively, whereas the net forcing in the atmosphere (ATM) varied from 17.27 to 23.16 Wm−2. Interestingly, the amount of energy trapped in the atmosphere due to eBC is 11.19 Wm−2 before LD and 8.56 Wm−2 during LD. It is concluded that eBC contributes almost 43–50% to the composite forcing. As a result, the eBC atmospheric heating rate decreased significantly (25%) when compared to before lockdown days to lockdown days.